2016
DOI: 10.1080/19475705.2016.1220023
|View full text |Cite
|
Sign up to set email alerts
|

GIS based landslide susceptibility mapping of northern areas of Pakistan, a case study of Shigar and Shyok Basins

Abstract: This study presents the use of geographical information system (GIS) datasets and methods to investigate landslide susceptibility in the rugged mountainous terrain of Shigar and Shyok Basins in northern areas of Pakistan. Study area is situated in Karakorum mountainous region where catastrophic landslides occur frequently and pose a serious threat to local living conditions. Landslide susceptibility index maps were prepared by combining four main indicators groups: (1) human induced parameters, which contain L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Integration of different models for the identification of probable areas of landslide occurrence through LSM is a recognized approach for sustainable risk mitigation [18]. Access to accurate inventory data along with hazard conditioning factors using both data-driven and knowledge-based models have yielded successful results for LSM in different studies [19][20][21]. Several studies have used expert knowledge-based models for conducting LSM.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of different models for the identification of probable areas of landslide occurrence through LSM is a recognized approach for sustainable risk mitigation [18]. Access to accurate inventory data along with hazard conditioning factors using both data-driven and knowledge-based models have yielded successful results for LSM in different studies [19][20][21]. Several studies have used expert knowledge-based models for conducting LSM.…”
Section: Introductionmentioning
confidence: 99%
“…<5˚, 5˚ -15˚, 15˚ -30˚, 30˚ -45˚ and >45˚. According to [6], highest landslide susceptible class is 30˚ -40˚ slope angle which consists of steep slopes. The aspect map (Figure 2 to certain elevations [10].…”
Section: Data Acquisition and Preparation Of Causative Factorsmentioning
confidence: 99%
“…Even though Gilgit Baltistan is highly susceptible to landslides, merely a few studies have been carried out in the region [6]. Moreover no such studied has been conducted in district Ghizer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, landslide density increases with increase in steepness (Pradhan et al, 2010). Kartiko et al (2006) found that more than half of the landslides occur in areas where the slope is greater than 25 %. Curvature expresses the shape of the slope.…”
Section: Introductionmentioning
confidence: 99%